STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KEJENUHAN BELAJAR PADA SISWA DI SMA NEGERI 10 GOWA - Novianti, Irka; Malli, Rusli; Muthahharah, Sitti (LPPM Universitas Islam 45, 2024)
In the education process, there are often cases, one of which is learning saturation. The meaning of saturation is literally dense or very full, not only that, saturation can also mean boredom. If a learner in the educational process faces such a boredom incident, the matter may make the learner feel that he is wasting his time. Learning boredom is time spent studying, but there are no results. The purpose of this study was to determine and analyze the strategy of Islamic religious education teachers in overcoming learning saturation in students at SMA Negeri 10 Gowa. The research method applies a qualitative approach with the type of field research. This research uses primary sources derived from documentation and interviews with teachers and students of SMA Negeri 10 Gowa. The results showed that about the strategy of Islamic religious education teachers in overcoming learning boredom in students at SMA Negeri 10 Gowa through varied learning methods, doing ice breaking, building a conducive learning atmosphere, providing rewards, conducting learning outside the classroom and building family relationships between teachers and students